Methods of Utilizing Tropical Peat Land for Housing Scheme - Youventharan, Duraisamy; Bujang, B. K. Huat; Azlan, A. Aziz (Science Publications, 2007)
This paper discusses some of the methods and recent technologies in utilizing cheap marginal land such as tropical peat for housing scheme. Buildings on peat are usually suspended on piles, but ground around it may still settle. Therefore a suitable method of construction should be tackle to overcome serious problem such as localized sinking and slip failure, massive primary and long term (creep) settlement. With the ever increase in the cost of living and the decrease in suitable land for construction, avoidance of marginal tropical peat soil is never going to be the popular choice among the developers and town planners. This paper gives some insights on the construction methods that could be possibly employed to develop marginal ground such as tropical peat soil.